COVID-19 associated with diabetes and other noncommunicable diseases led to a global health crisis - Barone, Mark Thomaz Ugliara (Diabetes Res Clin Pract, 2021)
COVID-19 has gravely threatened high-risk populations, such as people with diabetes and other noncommunicable diseases, leading to disproportionate hospitalizations and deaths worldwide. It is well documented from previous outbreaks that diabetes increases the risk for poor outcomes due to SARS infection. In the present review, we bring evidence that the country and global level health crisis caused by COVID-19 could have been avoided or extremely minimized if measures to protect high-risk populations were implemented timely. In addition to general lockdowns, testing, tracing, isolation and hygiene measures, other specific interventions for diabetes and comorbidities management were shown crucial to allow the continuation of care services during the pandemic. These interventions included: teleconsultation, digital remote education andmonitoring, e-prescriptions, medicine delivery options, mobile clinics, and home point-of-care tests. In conclusion, we recommend prompt actions to protect the most vulnerable groups, valuing knowledge and experiences from previous outbreaks and lessons learned during the COVID-19 pandemic, in order to shield communities, health systems and the global economy.